Touch in the Helping Professions Research, Practice and Ethics - Rovers, Martin; Malette, Judith; Guirguis-Younger, Manal (Health & Society, 2018)
Inappropriate touch cases have sparked public outcry and made headlines, but a discussion on the importance and ethics of positive, caring, appropriate touch in the helping professions such as teaching, nursing and counselling is long overdue.